1999
DOI: 10.1086/514286
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Hemorrhagic Fever, Kikwit, Democratic Republic of the Congo, 1995: Risk Factors for Patients without a Reported Exposure

Abstract: In 1995, 316 people became ill with Ebola hemorrhagic fever (EHF) in Kikwit, Democratic Republic of the Congo. The exposure source was not reported for 55 patients (17%) at the start of this investigation, and it remained unknown for 12 patients after extensive epidemiologic evaluation. Both admission to a hospital and visiting a person with fever and bleeding were risk factors associated with infection. Nineteen patients appeared to have been exposed while visiting someone with suspected EHF, although they di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 12 publications
3
91
0
2
Order By: Relevance
“…In addition, recent studies have demonstrated that pigs can be infected mucosally with EBOV and then transmit the virus to other, naive pigs (15) and to naive NHPs (16). The establishment of interspecies transmission without direct contact, in addition to past epidemiological observations (17), supports the notion that airborne EBOV transmission could potentially contribute, albeit at a low level, to the spread of disease during an outbreak.…”
Section: Importancementioning
confidence: 58%
“…In addition, recent studies have demonstrated that pigs can be infected mucosally with EBOV and then transmit the virus to other, naive pigs (15) and to naive NHPs (16). The establishment of interspecies transmission without direct contact, in addition to past epidemiological observations (17), supports the notion that airborne EBOV transmission could potentially contribute, albeit at a low level, to the spread of disease during an outbreak.…”
Section: Importancementioning
confidence: 58%
“…These arthropathies result from either viral replication or the deposition of immune complexes in joint tissue. In other studies, antibody levels were greater among convalescents with arthralgias, indicating (indirectly) the role of persistent low-level antigenic stimulation (Dowell and others 1999;Rodriguez and others 1999;Roels and others 1999;Rowe and others 1999).…”
Section: Immunological Manifestations Among Survivors Of Ehfmentioning
confidence: 77%
“…9 We considered the risks of transmission via food crops and via disposal of waste directly onto the ground to be low -primarily because of the lack of evidence of such transmission 40 but also because solar radiation and other environmental stressors, such as antiviral microbial activity in soils, may rapidly inactivate the virus. However, it is worth noting that there is evidence highlighting contact with raw sewage as a transmission route for many other pathogens.…”
Section: Cleaning and Disinfecting Of Nonhuman Wastementioning
confidence: 99%